Design and development of a dancing robot - Lim, Boon Leng. (2010)
Technological advancements in the field of robotics have enabled the creation of powerful, yet affordable model of humanoid robots. Robonova-1, by Hitec Robotics is considered as one of the most popular among these robots. However the center of gravity (CG) of these robots is located at the upper torso. This greatly affects the stability and restricts the motion of the robot. The Bluetooth technology and vision system of Robonova-I robots has already been perfected by previous researches. This report will focus on the imparting of intelligence to the robot as well as explore the potential for human-robot interaction and the improvement of the robot center of gravity (CG). This could be achieved with the support of CMUcam vision technology and the introducing of continuous servos. In this project, an RN-1 robot is modified in such a way that, the original head of the Robonova-1 is replaced by the tilt mechanism with the CMUcam3 attached to it. Camera function enables the robot to identify and track objects of various colors, monitor the movement of object and then process the image for further reaction. This paper also discusses modification of two standard HS- 5475HB servo to be used as continuous servo to control the two drive wheels which is secured on the robot platform. With the implementation of continuous servo, it allows the robot to be able to perform rotation of 360 degree left or right movement as well as moving forward or backward thus enhancing the robot stability.